2017
DOI: 10.7717/peerj.3345
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of the Mini Nutritional Assessment Short Form (MNA-SF) in a free-living elderly population: a cross-sectional study

Abstract: BackgroundVarious scales have been used to perform a quick and first level nutritional assessment, and the MNA is one of the most used and recommended by experts in the elderly in all areas. This scale has a short form, the MNA-SF, revised and validated in 2009, which has two versions: the BMI-MNA-SF contains the first six items of the full scale including Body Mass Index while the CC-MNA-SF includes Calf Circumference instead of BMI.ObjectiveTo evaluate the predictive ability for nutritional status of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
(29 reference statements)
2
25
0
Order By: Relevance
“…GA assesses age‐related vulnerabilities or domains that are predictive of morbidity and mortality in older adults with cancer . In our study, GA domains were assessed using validated tools and cutoffs and included comorbidity , functional status , physical performance , cognition , instrumental social support (e.g., someone to help if you were confined to bed) , polypharmacy , psychological health , and nutrition (supplemental online Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…GA assesses age‐related vulnerabilities or domains that are predictive of morbidity and mortality in older adults with cancer . In our study, GA domains were assessed using validated tools and cutoffs and included comorbidity , functional status , physical performance , cognition , instrumental social support (e.g., someone to help if you were confined to bed) , polypharmacy , psychological health , and nutrition (supplemental online Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Nutrition Risk Screening 2002 (NRS 2002), Malnutrition Universal Screening Tool (MUST), Mini Nutrition Assessment Shortcut (MNA-sf), and Nutrition Risk Index (NRI) are currently commonly used clinical nutrition screening methods [5][6][7][8]. Previous studies have validated the role of these non-disease-specific nutritional risk screening (NRS) tools to identify nutritional risks in hospitalized patients with multiple diseases [9,10]. However, little research had been reported on the use of these NRS tools for a specific disease: COVID-19, which has the potential to put patients at nutritional risk.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis was performed in correspondence with the MNA, taking into account certain initiating factors of eating disorders in the population of older people. The studies of Montejano Lozoya et al [10] were conducted among 660 seniors staying at home, with the use of a full version of the MNA scale, the MNA-SF and its 2 variations: BMI-MNA-SF and CC-MNA-SF. The average results obtained on the afore-mentioned scales proved high.…”
Section: Resultsmentioning
confidence: 99%
“…A disordered nutritional status could stem from a range of medical, psychological and social factors [1]. It also pertains to institutionalisation, hospitalisation and inhabiting rural areas, which finds confirmation in a variety of studies [1, 14, Selected anthropometric measurements and mini nutritional assessment in relation to some predictive factors of undernourishment in the elderly which CC may be applied at primary care facilities thanks to the shorter measurement time and a smaller number of devices than in the case of BMI assessment [10]. Similar associations as far as a certain degree of underestimation while using the MNA-SF-CC is concerned are made in the studies conducted by Kaiser et al [19] who assessed 675 senior citizens from various backgrounds, both those staying at rehabilitation centres or nursing homes and those staying at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation